SOCIAL ENTREPRENEURSHIP AND ITS IMPACT ON SOCIETY: A QUALITATIVE STUDY OF BUSINESS MODELS AND SUSTAINABLE GROWTH - Fauzi Hidayat, Lutfi (Journal of Islamic Economic Development, 2024)
This study explores social entrepreneurship and its impact on society through a qualitative investigation into business models and sustainable growth. Successful social entrepreneurship business models often incorporate innovation, collaboration with local stakeholders, and the use of technology to increase efficiency and scalability. Sustainable growth is achieved through smart resource management, development strategies and diversification of revenue sources. In addition, the ability to address social challenges and adapt to changes in the external environment also plays an important role in the sustainability of social enterprises. The objective of this research is to understand how social entrepreneurship business models are designed and implemented and how they contribute to sustainable growth.This research uses a case study methodology to analyze several successful social enterprises in areas such as education, health and the environment. Data was collected through document analysis. The study concludes that social entrepreneurship not only has the potential to address various social and economic challenges, but also contributes to inclusive sustainable development. The findings have important implications for policy makers, business practitioners and academics in developing strategies to support and strengthen the social entrepreneurship ecosystem.